Adipose-derived stromal vascular fraction (SVF) for the treatment of androgenic alopecia (AGA): a systematic review - Mantovani, Gian Piero; Marra, Caterina; De Maria, Federico; Pinto, Valentina; De Santis, Giorgio (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Androgenetic alopecia (AGA) is a common chronic, hereditary, cutaneous and androgen-dependent condition. Low self-esteem and negatively impact quality of life are often consequences of AGA. Clinical treatment of AGA using SVF (Stromal vascular fraction) has been effective. In fact, hair follicle is affected by various environment factors and one of the most important factors is the vascularity of the scalp which is itself affected bySVF.Methods: During October 2022 we carried out a systematic review to identify all scientific publications discussing about hair loss treatment with stromal vascular fraction or adipose stem cell. We selected 140 articles. After screening process, we kept 9 articles complying with inclusion criteria. Results: No serious adverse events were reported in all studies. Despite standardized protocol was not found, all studies reported a statistically significant increase in the number (density) of hair after SVF treatment. Two studies found a significant improvement at pull test. An increase of hair diameter was noticed after treatment. The combination between medical therapy and SVF proved to be advantageous.Conclusions: SVF is nowadays at the center of studies in the field of regenerative medicine due to its potential applications in many branches of medicine and surgery. The initial results are very promising but furthermore studies are necessary to establish a methodical and systematic research capable of demonstrating its real benefits and the creation of homogenous treatment protocols.